EMT Model Validation Throughout the Life Cycle of Wind Power Plants Based on Type IV Turbines: Experiences and Recommendations - Gabriel Miguel Gomes Guerreiro; Ranjan Sharma; Pankaj Kumar; Sulav Ghimire; Frank Martin; Pramod Ghimire; Guangya Yang (IEEE Access)
The validation of Electromagnetic Transients (EMT) models is essential for ensuring the accuracy of grid compliance and stability studies. However, there is still room for improvement in understanding the processes and a lack of standards for EMT model validation, especially after the commissioning of a wind power plant. This paper addresses this gap and presents experiences and recommendations for EMT model validation from an Original Equipment Manufacturer (OEM) perspective throughout the entire life cycle of offshore type IV wind turbines and wind power plants. The paper showcases different perspectives on model validation, including methodologies, requirements, and accuracy. It illustrates the process of wind turbine level model validation during design or pre-commissioning with practical examples and also demonstrates the wind power plant level model validation for two operational plants. In conclusion, the paper addresses various challenges and recommendations for model validation related to measurement location placement, data acquisition, aggregation methods, preprocessing, turbine connection status, and operating conditions at the time of the fault.